Elderly care centers challenges and difficulties in Malaysia: a case study of Pertubuhan Kebajikan Darul Insyirah - Mohd Yusoff, Syarah Syahira; Hassan, Rusni; Salman, Syed Ahmed (Science Press / Chinese Physical Society, 2023)
Malaysia is a developing nation experiencing a significant rise in the proportion of its elderly population. This phenomenon occurs worldwide and has excellent repercussions for every facet of human life. Even though the management of currently registered elderly care centers in Malaysia is working hard to provide the best possible amenities and services to the country's elderly population, a significant number of goals still need to be achieved because the phenomenon of people living longer is a worldwide trend. This study investigates the difficulties senior care facilities in Malaysia face to better serve their patients. It is a topic of significant concern in Malaysia, and efforts are currently being made to solve the rapidly aging population problem. This research will look into the significant challenges and difficulties that Pertubuhan Kebajikan Darul Insyirah in Malaysia is currently up against and the potential solutions. It was decided that the qualitative approach would suitable to address the issue. An interview has been requested for each of the five members of the Darul Insyrah staff currently employed there. A focus group was incorporated into this study so that the required data could be gathered for the investigation being conducted. The interviewees bring up various problems and difficulties that Pertubuhan Kebajikan Darul Insyirah experiences. In conclusion, the researchers offer suggestions for overcoming these problems and obstacles.